An updated cost-effectiveness analysis of pazopanib versus sunitinib as first-line treatment for locally advanced or metastatic renal cell carcinoma in Italy. (1st December 2020) - Capri, Stefano; Porta, Camillo; Condorelli, Claudia; Premoli, Eleonora; Khare, Ankur; Kalra, Manik; Modi, Niraj; Ratto, Barbara
Abstract: Objective: To assess the cost-effectiveness of pazopanib versus sunitinib as a first-line treatment for patients with metastatic renal cell carcinoma (mRCC) from an Italian National Health Service perspective, considering the evolving Italian landscape in terms of new reimbursement agreements trend. Methods: This analysis is an update of the previously published cost-effectiveness analysis to incorporate recent 2019 costs and additional changes regarding drug discounting. A partitioned-survival analysis model with three different health states (progression-free survival, post-progression survival, and dead) was utilized. Outcomes included progression-free life years, post-progression life years, overall life years, quality-adjusted life years (QALYs), and costs calculated for both treatments. Cost-effectiveness was assessed in terms of incremental costs per QALY gained and the net monetary benefit (NMB) of pazopanib versus sunitinib. In the base case analysis, a time horizon of 5 years was used and future costs and QALYs were discounted at a 3% annual discount rate. An impact of methodological and parameter uncertainly on base case results was evaluated using probabilistic and deterministic sensitivity analyses. Results: In the base case, pazopanib had higher QALYs (+0.060) at lower costs (−€5, 857) versus sunitinib, hence it dominated sunitinib. At willingness-to-pay thresholds of €30, 000 and €50, 000 per QALY, the NMB with pazopanib were €7, 647 and €8, 841 per patient, respectively, versus sunitinib. The probability that pazopanib is cost-effective versus sunitinib was estimated to be 97.5% at a cost-effectiveness threshold of €20, 000, 95.4% at a threshold of €30, 000, and 90.2% at a threshold of €50, 000 per QALY. Cost-effectiveness results were robust to changes in key parameter values and assumptions as demonstrated by deterministic sensitivity analyses. Conclusions: Pazopanib is likely to represent a cost-effective treatment option compared with sunitinib as a first-line treatment for patients with metastatic RCC in Italy.